Aerodynamic significance of mass distribution on diverse samara descent behaviors - Zhao-Bang Hou; Jun-Duo Zhang; Yun-Da Li; Yong-Xia Jia; Wei-Xi Huang (Communications Engineering)
Abstract Samaras, or wing seeds, feature fibrous appendages that act as wings to enable wind-driven dispersal. Diversity in morphologies and structures subtly contributes to the flight patterns of various seeds, thereby serving as a key factor in the reproductive strategies of plants. To explore the mechanisms underlying various samara flight behaviors, we proposed an effective framework by manipulating the mass distribution on a plate to mimic various three-dimensional descent behaviors of samaras. Through this approach, we experimentally identified and characterized four distinct flight modes. The three-dimensional vortical structures were then numerically analyzed to gain insights into the samara-inspired flight behaviors. Our study innovatively demonstrates how strategic mass distribution in samaras leads to diverse flight behaviors that leverage vortices to enhance seed dispersal, offering a fresh perspective for the design of biomimetic fliers.